Impact of visceral fat on surgical complications and long-term survival of patients with gastric cancer after radical gastrectomy. Issue 3 (March 2018) - Wang, Su-Lin; Ma, Liang-Liang; Chen, Xi-Yi; Zhou, Dong-Lei; Li, Bo; Huang, Dong-Dong; Yu, Zhen; Shen, Xian; Zhuang, Cheng-Le
Abstract Background/objectives The aim of this study was to examine the impact of visceral fat on surgical complications and long-term survival for patients undergoing radical gastrectomy. Subjects/methods From 2009 to 2013, 859 patients who underwent curative resection for gastric cancer were enrolled from a prospectively maintained database. Visceral fat area (VFA) was assessed by preoperative CT scans. Patients were divided into two groups by VFA. Perioperative variables and postoperative outcomes were compared between the high VFA group and low VFA group. Univariable and multivariable analysis were performed to investigate independent risk factors of postoperative complications and survival. Results Some 859 patients were included in the study, 308 of whom were classified as high VFA. High VFA was correlated with advance age (P = 0.020), higher albumin levels (P = 0.001), hemoglobin levels (P < 0.05), ASA grade (P = 0.043) and Charlson Comorbidity Index (P = 0.004). Relative to patients with low VFA, those with high VFA had longer surgical durations (P = 0.004), higher rate of postoperative complications (P = 0.004), and longer hospital stays (P = 0.004). High VFA was identified as the only determinant for surgical complications by logistic regression analysis (OR, 2.236, 95% CI, 1.537–3.254;P < 0.001). Cox proportional hazards regression revealed no correlation between VFA and overall survival (OS) or disease-free survival (DFS). Conclusions Increased VFA independently predicts surgical complications in patients after gastrectomy. However, VFA is not a prognostic biomarker of OS or DFS in patients with gastric cancer.